GULEMAN (ELAZIĞ) KROM YATAĞI ÇEVRESİNDEKİ SULARDA LEMNA GİBBA L. VE LEMNA MİNOR L. KULLANILARAK CR, Nİ VE CO ALIM KAPASİTELERİNİN İNCELENMESİ - DOĞAN, İBRAHİM METE (Fırat Üniveristesi, 2015)
Sucul bitkiler maden sularındaki ağır metalleri gidermek için oldukça ucuz ve etkilidir. L. gibba ve L. minor bitkilerinin Guleman krom yatağından gelen maden suları içerisindeki Cr, N ve Co metallerinin kaldırma kapasiteleri incelendi. L. gibba and L. minor bitkileri botanic bahçesinden toplandı daha sonra maden sularının bulunduğu gölalanı içerisine 8 gün boyunca yerleştirildi. Bu bitkiler her gün düzenli olarak hasat edildi ve laboratuvara taşındı. Laboratuvarda, bitkiler yıkandı, kurutuldu ve Acme Analiz Laboratuvarında (Kanada) Cr, Ni ve Co için ICP-MS'de analiz edildi. Analiz sonuçlarına göre; Cr için L. minor 8. günde % 398, L.gibba'da ise 8. günde % 196; Ni için L.minor 8. günde % 1473, L. gibba'da ise 8. günde % 307; Co için L. minor 8. günde % 223, L. gibba'da ise 8. günde % 166 gibi akümülasyonlar gözlendi.

Aquatic plants are quite cheap and effective at removing the heavy metals in tailing/gallery waters. L. gibba and L. minor plants were investigated for their removing capacities Cr, Ni and Co in mining water which is drained from the Guleman chromite mining area in Elazığ, Turkey. L. gibba and L. minor were collected from a botanic garden, then acclimated and fed to the mining water in situ for 8 days. These plants were harvested every day and continually transported to the laboratory. Plants were washed, dried, and were analyzed by ICP-MS to determine the amounts of Cr, Ni and Co in Acme Analytical Lab., Canada. The concentrations of Cr in L. gibba L. and L. minor L. were accumulated as a function of time, for 8 days, and showed very high performances % 196 for L. gibba L., and % 398 for L. minor L. The highest concentrations of Ni in L. gibba L. and L. minor L. were accumulated in 307% and 1473% performances, respectively, for 8 days. L. gibba L. and L. minor L. showed 166% and 223% performances, respectively for 8 days.
Cr, Ni and Co accumulations by using Lemna minor and Lemna gibba in waters around Guleman chromite deposits, Elazig
Keywords: Jeoloji Mühendisliği